2021
DOI: 10.1038/s41598-021-86857-0
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic variants in the SORD gene are one of the most common causes of hereditary neuropathy among Czech patients

Abstract: Recently, biallelic variants in the SORD gene were identified as causal for axonal hereditary neuropathy (HN). We ascertained the spectrum and frequency of SORD variants among a large cohort of Czech patients with unknown cause of HN. Exome sequencing data were analysed for SORD (58 patients). The prevalent c.757del variant was tested with fragment analysis (931 patients). Sanger sequencing in additional 70 patients was done. PCR primers were designed to amplify the SORD gene with the exclusion of the pseudoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…This discovery was further replicated in CMT patient cohorts in the Czech Republic, 4 Spain, 5 and China 6‐8 . Typically, affected individuals carry the nonsense SORD c.757del variant (rs1042079) in a homozygous or compound heterozygous state, leading to a loss of SORD function 3‐8 …”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…This discovery was further replicated in CMT patient cohorts in the Czech Republic, 4 Spain, 5 and China 6‐8 . Typically, affected individuals carry the nonsense SORD c.757del variant (rs1042079) in a homozygous or compound heterozygous state, leading to a loss of SORD function 3‐8 …”
Section: Introductionmentioning
confidence: 84%
“…Our novel use of ONT long‐read sequencing confirmed that these variants were biallelic and were present in the SORD gene, rather than the homologous pseudogene SORD2P . Whilst previous cohort studies identified biallelic SORD mutations affecting 3‐10% of the CMT2/dHMN cohort, 3‐8 we identified a single individual from 97 exomes of individuals with a clinical CMT2/dHMN diagnosis (1.0%). Although this may represent the true frequency of biallelic SORD mutations in our Australian cohort, it has been speculated that commonly used next‐generation sequencing pipelines are unable to accurately detect SORD c.757del due to the SORD2P gene 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since biallelic mutations in the sorbitol dehydrogenase (SORD) gene were first described in May 2020, 14 mutations have been identified to our knowledge (4)(5)(6)(7). SORD-related neuropathy has been reported as one of the most frequent causes of autosomal recessive CMT2 and dHMN (4).…”
Section: Introductionmentioning
confidence: 99%
“…SORD -related neuropathy has been reported as one of the most frequent causes of autosomal recessive CMT2 and dHMN ( 4 ). The prevalent mutation is c.757delG (p.A253Qfs * 27), and almost all previously reported mutations in patients with CMT and dHMN are related to this variant, either in homozygous or heterozygous states ( 4 , 5 , 7 ), except one Chinese patient with dHMN harboring the compound heterozygous c.404 A>G and c.9081 + G>C mutation ( 6 ). Most of the mutations in SORD are frameshift or splicing mutations, indicating a loss of function of sorbitol dehydrogenase, which is a key enzyme that converts sorbitol to fructose.…”
Section: Introductionmentioning
confidence: 99%